2007
DOI: 10.4315/0362-028x-70.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Novel Campylobacter Isolation Method Using Hydrophobic Grid Membrane Filter and Semisolid Medium

Abstract: Culture procedures for isolation of thermophilic campylobacters from food matrices are complex, labor intensive, and time-consuming. Most available methods include the use of antibiotics as selective agents to prevent the growth of competing microflora. A simple procedure for isolation of thermophilic campylobacters after enrichment in Rosef's enrichment broth was developed using a hydrophobic grid membrane filter (HGMF) on semisolid medium (SSM). SSM contains no antibiotics, and the HGMF physically separates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…17 The outbreak of Campylobacter species in chicken meat in other countries also suggests a contamination level of 30 to 90 percent. The contamination levels in different countries were as follows: Turkey with 92/8%, 18 Korea with 68/3%, 11 Canada with 62/4%, 12 Japan with 60%, 6 Ireland with 49/90%, 13 and Pakistan with 48%. 14 Despite having many studies reporting the prevalence of Campylobacter species contamination in poultry, there are few studies highlighting on the edible offal contamination to the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The outbreak of Campylobacter species in chicken meat in other countries also suggests a contamination level of 30 to 90 percent. The contamination levels in different countries were as follows: Turkey with 92/8%, 18 Korea with 68/3%, 11 Canada with 62/4%, 12 Japan with 60%, 6 Ireland with 49/90%, 13 and Pakistan with 48%. 14 Despite having many studies reporting the prevalence of Campylobacter species contamination in poultry, there are few studies highlighting on the edible offal contamination to the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…12 Such high prevalence could be attributed to high temperature creating favorable conditions for the bacteria growth of and transferring of infection by insects. The overall results of this study on chicken meat and its edible offal contamination to Campylobacter species showed that a relatively high number of samples especially the liver were infected with this pathogen.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The methods described in detail by Valdivieso-Garcia et al (44) were used for the isolation of Campylobacter. Briefly, 200 ml of the incubated Rosef's enrichment broth was used to inoculate a semisolid-medium plate with a quarter piece of Iso-Grid hydrophobic grid membrane filter (QA Life Sciences, Inc., San Diego, CA) and a 1-cm-diameter disk of filter paper (Schleicher & Schuell, Inc., Mandel, Guelph, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Conventional microbiology and selective culture techniques (Engberg et al, 2000;International Organization for Standardisation, 2005) -including various membrane filtration approaches (Bolton et al, 1988;le Roux and Lastovica, 1998;Mégraud, 1987;Steele and McDermott, 1984;Valdivieso-Garcia et al, 2007) have been developed for the isolation of Campylobacter spp. Selective media has been effective for the isolation of C. jejuni and C. coli (Engberg et al, 2000;Piersimoni et al, 1995); however, rarer and more elusive strains (e.g.…”
Section: Introductionmentioning
confidence: 99%